PERAN PEMILIK KEGIATAN (PENGGUNA ANGGARAN) DALAM UPAYA PERCEPATAN PEMBANGUNAN RUMAH ADAT (TAHAP II) KABUPATEN MUKOMUKO DAN ALTERNATIF PENANGANANNYA - Bewok, Apriansyah (Inersia: Jurnal Teknik Sipil, 2024)
In construction project work, there are usually several obstacles that can result in delays in the project work, both obstacles that have been taken into account and obstacles that are beyond the planner's calculations. These obstacles are the cause of delays in project completion, so that the project does not proceed according to plan, in this case in the Traditional House Construction project (Phase II) there can be delays both from a technical and non-technical perspective. This research was conducted as an effort to accelerate development and to obtain or understand the role of budget users to prevent delays in the Traditional House Development Project (Phase II). Keywords: the role of budget users in anticipating delays in the construction of traditional houses (phase II).